Why so few women, still?. - Tietjen, J.S (IEEE spectrum)
"Why are there so few women in engineering?" queried the e-mail from a male engineering student. As I listed the reasons put forth by various experts, the thought occurred to me: We've been working on this issue for 50 years now. If we really knew the answer, we would have solved it already. I've read lots of research on this topic and conducted many recruitment and outreach programs over the years to try to interest more women in studying engineering, and the conclusion I've reached is what I call "Jill's Theory": Engineering in the United States suffers from a huge image problem.